An introduction to vanadium redox flow batteries (VBFRs) and its monitoring - Popa, Iulian Ovidiu; Pastor-Flores, Pablo; Ibáñez Casao, Álvaro; Barreras, Felix (Jornada de Jóvenes Investigadores del I3A, 2022)
In the context of the changing energy production model, storage systems are needed to mitigate the intermittency of renewable sources. Redox flow batteries (RFBs) are electrochemical devices that allow energy to be stored and distributed when needed. This paper presents an overview of this technology.